Calculation of State Financial Losses as Evidence Against Corruption Crimes - Rahmayanti Rahmayanti; Masitah Pohan (Randwick International of Social Science Journal, 2022)
States losses can occur due to violations of law or negligence of state officials or civil servants. The high number of state losses will have a negative impact on the national economy, for this reason, efforts to recover from state losses are very necessary in saving the country's economy. State Losses Handled by the Corruption Eradication Commission (KPK) 2015-2020. Indonesia Corruption Watch (ICW) recorded the value of state losses due to corruption handled by the Corruption Eradication Commission (KPK) of Rp. 805 billion in 2020. This figure decreased by 87% from the previous year of Rp. 6.2 trillion. In Indonesia, the existence of state financial losses or the state's economy is an element of corruption offenses as regulated in Articles 2 and 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption (UU Tipikor). In accordance with Article 10 of Law Number 15 of 2006 concerning the Supreme Audit Agency (BPK Law) it is stated that the one who assesses or determines the existence of state losses is the State Audit Board (BPK). The purpose of this research is to find the right steps in mandating the government to maintain the balance of state finances as an effort to realize a transparent and responsible gove rnment system. This research uses descriptive analytical research methods, The approach used is normative and legal. The approach used in this study is the legal approach.